Analisis Perbaikan Sistem Distribusi untuk Meningkatkan Ketepatan Waktu dan Meminimalkan Biaya Pengiriman (Studi Kasus: PT. XYZ) - Daniel Nurhakim Agus Setiawan; Sajiyo Sajiyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Distribution is an important part of the logistics process, especially in the efficient delivery of goods from producers to consumers. This study aims to determine the optional distribution route of goods at PT.XYZ in order to minimize travel distance, as well as determine the best method in determining the route. The method used is the Vehicle Routing Problem (VRP) approach with three calculation techniques, namely saving matrix, nearest insert, nearest neighbor with validation and verification processes using LINGO 18.0 software. The result of the study show that the saving matrix method gets 7 routes and fleet allocations according to their maximum capacity, calculations from the three nearest insert methods get the shortest distance of 5098.1 km and savings in total distribution operational costs of Rp. 12,680,370 or 27.22% of the existing condition. This study is expected to be a recommendation for companies in distributing products.